(untitled) (Research, Society and Development, 2022)
The present article discusses pedagogical actions as a tool to raise awareness against feminicide. It is a part of an ongoing research developed in the Graduate Program in Teaching of Sciences and Humanities (PPGECH) in the Federal University of Amazonas - UFAM, Humaitá Unit - IEAA, whose focus is to think, in the school environment, the issues around gender violence as a possibility of awareness about feminicide in the State of Amazonas. For this, it was necessary: to contextualize the current picture of gender violence and feminicide in the State of Amazonas; to look at the guidelines suggested by the State Department of Education of Amazonas regarding the approach of this theme at school and to question the impacts of the practices aimed at fighting feminicide carried out in the school environment. The theoretical and methodological support was inspired by post-critical studies in education. The data were produced from a bibliographic and documental research. The main results suggest that it is extremely important to think of the school as a stage for discussing issues of school violence in the state of Amazonas, since cases of feminicide have grown considerably, including in these times of pandemic.